2018
DOI: 10.1093/mnras/sty3006
|View full text |Cite
|
Sign up to set email alerts
|

The radius inflation problem in short-period low-mass binaries: a large sample analysis

Abstract: Due to the recent increase in the availability of photometric time-series databases, the characterisation of low-mass eclipsing binaries for the study of their orbital and physical parameters is now possible in large samples and with good precision. We have identified and photometrically characterised a sample of 230 detached close-orbiting eclipsing binaries with low-mass main-sequence components in the Catalina Sky Survey. These low-mass stars have masses of M ≤ 1.0 M and orbital periods shorter than 2 days.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 37 publications
2
27
2
Order By: Relevance
“…For instance, the Gaia distance for CSS J162549.3+102124 is recovered if we assume a temperature ∼250 K higher than that used by us. Garrido et al (2019) characterized a sample of 230 detached closeorbiting eclipsing binaries with low-mass main-sequence components (M < 1 M ), orbital periods shorter than 2 d, and temperatures below 5720 K. They suggest a trend according to which low-mass stars would have inflated radii. Besides, they found that around 61 per cent of the sample has the secondary star more inflated in radius than the primary.…”
Section: Low-mass Stellar Parametersmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, the Gaia distance for CSS J162549.3+102124 is recovered if we assume a temperature ∼250 K higher than that used by us. Garrido et al (2019) characterized a sample of 230 detached closeorbiting eclipsing binaries with low-mass main-sequence components (M < 1 M ), orbital periods shorter than 2 d, and temperatures below 5720 K. They suggest a trend according to which low-mass stars would have inflated radii. Besides, they found that around 61 per cent of the sample has the secondary star more inflated in radius than the primary.…”
Section: Low-mass Stellar Parametersmentioning
confidence: 99%
“…Fig. 7 presents a mass-radius diagram for low-mass stars in binaries, where the objects found in this work are shown in red and blue, and the sample from Garrido et al (2019) in black and grey. The lines represent theoretical models from Baraffe et al (1998) with isochrones of 1, 5, and 8 Gyr for solar metallicity and helium abundance Y = 0.275.…”
Section: Low-mass Binaries and The Radius Inflation Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the physical parameters of M dwarfs are not easy to obtain and there are persistent discrepancies in theoretical estimations from stellar evolution models and observations regarding fundamental parameters, such as mass, radius and effective temperature in eclipsing binary systems, as well as in interferometry of single stars. The radius anomaly (see e.g., Tognelli et al, 2018) has been related to the effects of enhanced magnetic activity, a spotted stellar surface, or metallicity, which have been invoked to explain the observational-theoretical disagreement (see e.g., Higl and Weiss, 2017;Garrido et al, 2019;Kochukhov and Shulyak, 2019, and references therein).…”
Section: Introductionmentioning
confidence: 99%